2009
DOI: 10.1007/s00167-009-0962-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of tissue-engineered cartilage with BMP-7 gene to repair knee joint cartilage injury in rabbits

Abstract: Injured articular cartilage has a poor capacity for spontaneous healing. So far, satisfactory solution to this subsistent problem has not been found, but transgenic therapy may be a promising way. This study aims to evaluate the effectiveness of a tissue-engineered cartilage that was transfected with morphogenetic protein 7 (BMP 7) in repairing the cartilaginous defects of rabbit knee joints. Chondrocytes were transfected with BMP-7 gene (5 x 10(6) cells/ml), inoculated into the collagen-fibrin gel scaffolds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…FGF and BMP complexes had a significant b better therapeutic effect and induced lower levels of the inflammatory factor IL-1 compared to xenograft bones treated only with BMP. These results confirm that FGF is important for bone repair, as it promoted bone healing and reduced the inflammation reaction (Hou et al, 2009;Che et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…FGF and BMP complexes had a significant b better therapeutic effect and induced lower levels of the inflammatory factor IL-1 compared to xenograft bones treated only with BMP. These results confirm that FGF is important for bone repair, as it promoted bone healing and reduced the inflammation reaction (Hou et al, 2009;Che et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, regenerative medicine (RM) is a broader concept which, besides that previously discussed for TE, also considers the use of bioactive soluble molecules [13,14], stem cell technologies [15,16], prolotherapy (i.e. injectable regenerative techniques) [17], genetic therapeutic strategies [18], nanotechnologies and several medical devices.
Figure 1.TERM applications on the ankle joint.
…”
Section: Introduction: Fundamentals Of Tissue Engineering and Regenermentioning
confidence: 99%
“…BMP receives a lot of attention and is regarded as the strongest bone-and cartilage-inducing factor due to its ability to promote a variety of bone and cartilage defect repair and reconstruction [4,17]. Recent studies have confirmed that BMP-7 is a strong chemotactic component in cartilage cells produced by mesenchymal stem cells, and it can promote cartilage cells to secrete specific extracellular matrix (proteoglycans and collagen type II).…”
Section: Application Of Modulation Of Bmscs With Growth Factorsmentioning
confidence: 99%